A culturally tailored Internet cancer support group for Asian American breast cancer survivors: A randomized controlled pilot intervention study. (July 2017) - Chee, Wonshik; Lee, Yaelim; Im, Eun-Ok; Chee, Eunice; Tsai, Hsiu-Min; Nishigaki, Masakazu; Yeo, Seon Ae; Schapira, Marilyn M.; Mao, Jun James
Introduction: The necessity of culturally competent Internet Cancer Support Groups (ICSGs) for ethnic minorities has recently been highlighted in order to increase its attractiveness and usage. The purpose of this study was to determine the preliminary efficacy of a culturally tailored registered-nurse-moderated ICSG for Asian American breast cancer survivors in enhancing the women's breast cancer survivorship experience. Methods: The study included two phases: (a) a usability test and an expert review; and (b) a randomized controlled pilot intervention study. The usability test was conducted among five Asian American breast cancer survivors using a one-month online forum, and the expert review was conducted among five experts using the Cognitive Walkthrough method. The randomized controlled pilot intervention study (a pre-test and post-test design) was conducted among 65 Asian American breast cancer survivors. The data were analysed using content analysis and descriptive and inferential statistics including the repeated ANOVA. Results: All users and experts positively evaluated the program and provided their suggestions for the display, educational contents, and user-friendly structure. There were significant positive changes in the support care needs and physical and psychological symptoms ( p  < 0.05) of the control group. There were significant negative changes in the uncertainty level of the intervention group ( p  < 0.10). Controlling for background and disease factors, the intervention group showed significantly greater improvements than the control group in physical and psychological symptoms and quality of life ( p  < 0.10). Discussion: The findings supported the positive effects of ICSGs on support care needs, psychological and physical symptoms, and quality of life.